Cytokine-, Neurotrophin-, and Motor Rehabilitation-Induced Plasticity in Parkinson's Disease. (26th November 2020) - Policastro, Gabriella; Brunelli, Matteo; Tinazzi, Michele; Chiamulera, Cristiano; Emerich, Dwaine F.; Paolone, Giovanna
Abstract : Neuroinflammation and cytokine-dependent neurotoxicity appear to be major contributors to the neuropathology in Parkinson's disease (PD). While pharmacological advancements have been a mainstay in the treatment of PD for decades, it is becoming increasingly clear that nonpharmacological approaches including traditional and nontraditional forms of exercise and physical rehabilitation can be critical adjunctive or even primary treatment avenues. Here, we provide an overview of preclinical and clinical research detailing the biological role of proinflammatory molecules in PD and how motor rehabilitation can be used to therapeutically modulate neuroinflammation, restore neural plasticity, and improve motor function in PD.